2020
DOI: 10.4467/20843879pr.20.011.12266
|View full text |Cite
|
Sign up to set email alerts
|

The School Readiness of Six-Year-Old and Seven-Year- -Old Children as Measured by Intelligence and Development Scales (IDS) and Subjective Assessment of Mothers

Abstract: The presented study aimed at determining the school readiness of first-grade pupils by scores of standardised competence tests and the subjective assessment of mothers, checking possibilities to differentiate the results of preschoolers and pupils and correlations of both measurement methods. The Intelligence and Development Scales (IDS) and the Questionnaire of Subjective School Readiness Assessment by Parents (KGSD-R), with subscales analogous to those of IDS, were used. The three studied groups involved 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Previous research by our team (Michalska et al ., 2018;Michalska & Szymanik-Kostrzewska, 2020a) showed that the school readiness of children was at least average, and in terms of selected competences -high .…”
Section: Research Problemmentioning
confidence: 89%
See 3 more Smart Citations
“…Previous research by our team (Michalska et al ., 2018;Michalska & Szymanik-Kostrzewska, 2020a) showed that the school readiness of children was at least average, and in terms of selected competences -high .…”
Section: Research Problemmentioning
confidence: 89%
“…In the studies conducted so far (Michalska et al ., 2018;Michalska & Szymanik-Kostrzewska, 2020a), a moderate harmoniousness of the obtained results has been observed .…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Serede and Mwoma (2022) believe that parents define learning readiness as merely counting ability, object naming, and letter identification. Michalska et al (2018) highlight that an effective parent-teacher partnership is an important component for shaping the readiness of Grade R learners.…”
Section: P3mentioning
confidence: 98%